Internalization of Akhlakul Karimah Values Education at Pondok Pesantren Sunan Drajat Lamongan - Miftachul Ulum; Mahmud Manan; Muslihun Muslihun (Yayasan Darusssalam Bengkulu, 2026)
The purpose of this research is to analyze the implementation of strategies and methods in instilling the values ​​of akhlakul karimah, analyzing the process of internalization of the values ​​of akhlakul karimah at Pondok Pesantren Sunan Drajat Lamongan. The research method uses a case study. Researchers collected data through observation, in-depth interviews, and documentation from informants from the kiai, administrators, and students. The results of the study indicate that the tradition of knowledge at the Sunan Drajat Islamic Boarding School is based on the principle of learning originating from the guardian or kiai. The instillation of the values ​​of akhlakul karimah involves administrators and educators. This instillation of values ​​is carried out both formally and informally which are integrated vertically and horizontally in the governance of the Islamic boarding school through socialization, assignments and habituation. The findings of this research strengthen Peter L. Berger's theory in the process of stimulating values ​​which includes value transformation, value transactions and internalization.